Morphology Effect of the ZnO Surface via Organic Etchants for Photon Extraction in III-Nitride Emitters. (1st January 2017) - Oh, S.; Kim, S.; Shin, S.-C.; Su, P.-C.; Yoon, Y.-J.; Lee, K J.; Kim, S.-J.; Choi, H.; Park, S.-J.; Kim, K.-K.
Abstract : We demonstrate that the morphology effect on the ZnO surface using organic acids significantly improves the photon extraction efficiency of III-nitride emitters. Oxalic (C2 H2 O4 ), citric (C6 H8 O7 ), and formic (CH2 O2 ) acids were used for modulating the nanostructured surface of the ZnO layer with various shapes, including random nanoblocks, nanoholes, and nanorods. The transmittance of the nanostructured ZnO layer fabricated with formic acid for 3 min was 91% at 450 nm wavelength. The optical output power intensities of the emitters with the nanostructured ZnO surface layer were enhanced by 22.14%, 30.58%, and 22.46% with oxalic, formic, and citric acid, respectively, compared with the emitter with the flat ZnO layer.